Pendampingan Kelembagaan Petani Kopi pada Gapoktan Kamno Sari Mandiri (KSM) untuk Meningkatkan Produktifitas dan Kualitas Buah Kopi - Rian Ade Pratama (Universitas Muhammadiyah Mataram, 2025)
The Community Partnership Program (PKM) aims to address key issues faced by a group of coffee farmers in Kamno Sari Village, Jagebob District, Merauke Regency. The challenges include: (1) the absence of a formal institutional organization for coffee farmers (GAPOKTAN), (2) simultaneous harvesting of unripe (green) and ripe (red) coffee cherries, (3) suboptimal coffee bean drying processes, and (4) lack of understanding in direct coffee bean sales to café or coffee shop owners. The program fosters GAPOKTAN's independence in improving harvest productivity and direct sales by providing institutional knowledge, enabling members to develop assistance proposals for relevant agencies. The service team introduced financial management and marketing processes through transaction record-keeping and digital marketing. Activities were implemented in three stages: (1) institutional strengthening assistance for coffee farmers, (2) assistance in coffee cherry harvesting and post-harvest handling, and (3) technology transfer for coffee bean drying using metal drying tables. Seventeen participants took part in the program. A satisfaction survey showed 45% were very satisfied and 35% satisfied. All activities were successfully implemented and provided valuable knowledge for the Kamno Sari community.